2004
DOI: 10.1001/archderm.140.9.1109
|View full text |Cite|
|
Sign up to set email alerts
|

Skin Markers of Occult Spinal Dysraphism in Children

Abstract: To verify the diagnostic value of lumbosacral midline cutaneous lesions in asymptomatic children to detect occult spinal dysraphism (OSD) and to propose a practical approach for clinical investigations with respect to the type of cutaneous lesions observed.Design: Retrospective study of 54 children referred to the Department of Pediatric Dermatology between 1990 and 1999 for congenital midline lumbosacral cutaneous lesions.Setting: The private or institutional practices of participating dermatologists and pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
151
2
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(165 citation statements)
references
References 45 publications
5
151
2
6
Order By: Relevance
“…Ben-Sira et al used ultrasound to screen 254 neonates with midline skin stigmata 1 and found no pathological findings in any of the 109 cases with simple dimples. Other studies have also reported normal ultrasound results in most patients with sacrococcygeal dimples 6,7,12,15 and suggested that ultrasound screening is not necessary for infants with low-risk lesions, such as simple dimples. This finding contrasts with our study, in which 16.7% of the patients with simple dimples (both deep and shallow) had FTF, and 7% also had a low conus.…”
Section: Discussionmentioning
confidence: 95%
“…Ben-Sira et al used ultrasound to screen 254 neonates with midline skin stigmata 1 and found no pathological findings in any of the 109 cases with simple dimples. Other studies have also reported normal ultrasound results in most patients with sacrococcygeal dimples 6,7,12,15 and suggested that ultrasound screening is not necessary for infants with low-risk lesions, such as simple dimples. This finding contrasts with our study, in which 16.7% of the patients with simple dimples (both deep and shallow) had FTF, and 7% also had a low conus.…”
Section: Discussionmentioning
confidence: 95%
“…[1] Two or more congenital midline skin lesions are considered as the strongest markers of occult spinal dysraphism. [2] The present case shows that such simple lesions should be taken seriously if they occur simultaneously. On the other hand, Mongolian spots, sacral pits and dimples do not indicate a high risk of occult spinal dysraphism.…”
mentioning
confidence: 61%
“…2 When these lesions are present in association with a segmental and minimal growth hemangioma, the LUMBAR association may be present [L (lower body hemangioma, lipoma, and other cutaneous defects) U (urogenital anomalies and ulceration) M (myelopathy) B (boney deformities) A (anorectal malformations and arterial anomalies) R (renal anomalies)]. Approximately 30% of these patients will have associated tethered cord, and early diagnosis and treatment is necessary to lessen the risk of permanent neurologic damage [3][4][5] (Fig. 1).…”
Section: Infantile Hemangiomasmentioning
confidence: 99%